2012
DOI: 10.1177/1075547012441873
|View full text |Cite
|
Sign up to set email alerts
|

What, Me Worry? The Role of Affect in Information Seeking and Avoidance

Abstract: Guided by the risk information-seeking and processing model, this study examines positive and negative affect separately in their influence on informationseeking intentions and avoidance through structural equation analyses. The highlight is that information avoidance seems to be driven by positive affect, while information seeking seems to be more heavily influenced by negative affect. Another interesting finding is that informational subjective norms are positively related to both seeking and avoidance, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
269
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(292 citation statements)
references
References 36 publications
18
269
4
1
Order By: Relevance
“…The second section asked questions on information seeking behavior and its possible determinants. Some items (such as information seeking behavior [2,3]; information need [13]; perceived information gathering capacity [3]; informational subjective norms [1,3,38]; negative affective responses [2,13,38]; risk perception [43]) were measured on the basis of previous empirical studies, and current risk knowledge which was newly developed. The exact formulation of the items is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second section asked questions on information seeking behavior and its possible determinants. Some items (such as information seeking behavior [2,3]; information need [13]; perceived information gathering capacity [3]; informational subjective norms [1,3,38]; negative affective responses [2,13,38]; risk perception [43]) were measured on the basis of previous empirical studies, and current risk knowledge which was newly developed. The exact formulation of the items is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Negative affective responses lead to the awareness of a lack of risk knowledge [13,37], and subsequently, greater perceived information need [3,6,7,8,9,11,16,17], which ultimately prompts more active seeking behavior for risk information [3,4,6,8,13,16,17,19]. Many previous studies have also emphasized the negative affect; however, positive affective responses were also explored by Yang and Kahlor [38], and found that positive emotion could also be a direct determinant of risk information seeking behavior [39]. …”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…Yang and Kahlor [102] proposed that when people perceive that others expect them to know about environmental issues, they might purposely present themselves as knowing a lot about this issue. Thus, people who act according to social norms might have paid more attention to environmental information and actually developed a greater knowledge base.…”
Section: Environmental Knowledge (Ek)mentioning
confidence: 99%
“…Positive emotions about climate change were not related to behavioural intentions to seek out information about climate change. In contrast, individuals who reported feeling concerned, worried and anxious about climate change were less likely to avoid information about climate change, and more likely seek out such information (Yang and Kahlor 2012). Beattie et al (2010) had found that experimental participants do fixate on the carbon footprint of specific products like low energy light bulbs, where, of course, the information about carbon footprint is positive, rather than on the carbon footprint of products where the information is going to be obviously higher (like detergent).…”
Section: Optimism and Cognitive Processingmentioning
confidence: 90%
“…Attentional bias has been found to extend to the self-selection of information. One survey found that having positive or negative emotions about climate change was differentially related to information-seeking and avoidance behaviours (Yang and Kahlor 2012). People who felt excited, hopeful and happy about climate change were more likely to avoid or ignore information about climate change.…”
Section: Optimism and Cognitive Processingmentioning
confidence: 99%